LGG-11. Analysis of neurosurgical complications in pediatric supratentorial midline low-grade glioma – results from the German LGG studies. (3rd June 2022) - Weiß, Sarah; Schulz, Matthias; Kandels, Daniela; Driever, Pablo Hernáiz; Witt, Olaf; Thomale, Ulrich-Wilhelm; Gnekow, Astrid; le Simon, Michè
Abstract: OBJECTIVE: Around 80% of all pediatric low-grade glioma (LGG) patients undergo at least one tumor surgery. Interventions in the supratentorial midline (SML) are particularly challenging due to the proximity of eloquent areas, yet associated complications are scarcely reported. We investigated the frequency of neurosurgical complications and related impairments and aimed at identifying risk factors for their appearance related to patient characteristics or the procedure. PATIENTS AND METHOD: Records were retrospectively analyzed from 321 patients with SML-LGG from the successive multicenter German LGG studies, who underwent neurosurgery at 63 hospitals between May 12th, 1998 and June 27th, 2020. RESULTS: 543 operations (235 resections, 168 biopsies, 140 non-tumor interventions) were performed on 321 patients (54% male, median age 9 years, 11% NF1 positive, 43% visual pathway glioma). Surgical mortality rate was 0, 93% (n=3). Applying the Drake classification postoperative surgical morbidity was observed in 259 cases (47, 7%), medical morbidity in 103 cases (19%). 30-day persistence rate of newly developed neurological deficits was 44, 8% (65/165 cases); neuroendocrine impairment affected 57 patients (17, 8%), visual deterioration 34 (10, 6%). Complications/impairments following resections were associated with patient age below 3 years at operation, tumor volume above 80 cm 3, presence of hydrocephalus prior to surgery, complete resection, intervention in centers with fewer reported resections and surgery performed between 1998-2006 by univariate analysis. In contrast, the neurosurgical approach, tumor location, NF1 status as well as previous antineoplastic treatment were not associated with the frequency of complications. Regarding biopsies, open biopsies showed significantly more surgery-associated complications/impairments compared with stereotactic procedures. CONCLUSIONS: Neurosurgery-associated complications and impairments were frequent in pediatric patients with supratentorial midline LGG undergoing open surgery in the German LGG-studies. We identified six patient- and institution-associated factors that may increase the risk for surgical complications. Skills at the treating center and extent of resection should be considered appropriately prior to intervention.